VLSI-SoC : design for reliability, security, and low power : 23rd IFIP WG 10.5/IEEE International Conference on Very Large Scale Integration, VLSI-SoC 2015, Daejeon, Korea, October 5-7, 2015, Revised selected papers /: design for reliability, security, and low power : 23rd IFIP WG 10.5/IEEE International Conference on Very Large Scale Integration, VLSI-SoC 2015, Daejeon, Korea, October 5-7, 2015, Revised selected papers. (2016) - Unknown
No abstract available